The Effect of Dual Pricing and Promotional Strategies on Traders Income in Tourism Villages, Samosir Regency - Nicholas Marpaung; Onan Marakali Siregar (Indonesian Journal of Business Analytics, 2023)
One of the pricing methods is dual pricing, but many consumers still find it unfair. Dual pricing is an easy and realistic strategy for increasing income for small companies or traders. This is especially true for small traders who are not yet familiar with sufficient marketing strategies. Traders in the Tourism Village of Samosir Regency currently apply double prices in trading every day because they don't have an adequate marketing strategy, especially promotions. The purpose of this study is to find out how the income of traders in five tourist villages in Samosir Regency is affected by dual prices and promotion strategies. This study uses a quantitative approach, and data is processed using SPSS. The promotion strategy does not have a significant effect on the income of traders in the Tourism Village of Samosir Regency, but dual pricing has a positive and significant effect. This shows that traders use Dual Pricing as the main strategy to increase their business revenue. However, because merchants do not have a lot of marketing knowledge and enough marketing channels to sell their goods, the promotion strategy is not very effective. However, the results of the simultaneous test show that the Dual Pricing and Promotion Strategy Variables have a significant correlation with the income of traders in the Tourism Village of Samosir Regency. In addition, this shows that although the independent variables do not have the same strong effect partially, the marketing strategy and dual pricing have a significant correlation to income.